The Role of Special Forces in Peace Missions: A Focus on MINUSMA within the African Context - Bester, Louis (Scientia Militaria - South African Journal of Military Studies, 2023)
Special forces have always captured the imagination of the world. This comes as no surprise, as there is a lot of literature and movies on special forces available. The terror attacks on 11 September 2001 in the United States of America, and the subsequent declaration by George W. Bush of a Global War on Terrorism, has brought the special forces of the United States and other Western powers out of the shadows and into the limelight as the force of choice to combat the new security threat. It also focussed the international concern on the security threats of ungoverned spaces, failed states, and the use of terror. This in turn created a merging of failed states and counter-terrorism agendas, which resulted in a powerful new framework for humanitarian actors. Third party interventions in the form of the United Nations Multidimensional Integrated Stabilisation Mission in Mali (MINUSMA), to mention but one example, appeared. The subsequent deployment of European special forces to Mali in 2013 as part of MINUSMA was in an effort to restore constitutional order to the Malian government. The mission is still ongoing and thus relevant as a case study to relate the role of special forces to peace missions. The aim of the article is to explore the role of special forces in peace missions, using the role of European Special Forces in MINUSMA as case study.